Through the hoop : understanding the person-job-organization-environment fit theory to attract sport managers to a new NBA franchise - Ingerson, Lynley; Naraine, Michael L. (London : Human Kinetics, Inc., 2019)
This case study explores the elements of fit between individuals, job opportunities, an NBA franchise, and its environment. Developing the right job descriptions for attracting a talented team of sport managers to Buffalo, who are capable of managing the highly competitive Buffalo Braves basketball franchise, is fundamental to getting the fit right. The focus of this case includes exploring motives and rewards for the various management roles devised, understanding the concept of 'fit' in hiring talented and innovative sport managers, developing clear responsibilities, and effectively aligning the expectations within a psychological contract between each new management role and organization at the Buffalo Braves.
Originally Published InIngerson, L., & Naraine, M. (2019). Through the Hoop: Understanding the Person-JobOrganization-Environment Fit Theory to Attract Sport Managers to a New NBA Franchise. Case Studies in Sport Management, 8(S1), S7-S14.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports administration